2001
DOI: 10.1162/089892901753294365
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Corpus Callosum and Interhemispheric Transfer of Somatosensory Information: An fMRI and Neuropsychological Study of a Partially Callosotomized Patient

Abstract: Interhemispheric somatosensory transfer was studied by functional magnetic resonance imaging (fMRI) and neuropsychological tests in a patient who underwent resection of the corpus callosum (CC) for drug-resistant epilepsy in two stages. The first resection involved the anterior half of the body of CC and the second, its posterior half and the splenium. For the fMRI study, the hand was stimulated with a rough sponge. The neuropsychological tests included: Tactile Naming Test (TNT), Same-Different Recognition Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 51 publications
8
49
0
2
Order By: Relevance
“…Given that this task is dependent on the interhemispheric transfer of memorized proprioceptive feedback prior to making an accurate matching movement (Fabri et al 2001;Sperry et al 1969), one may logically conclude that subjects more readily transferred this information from the left to the right hemi- sphere. This directional bias with respect to the interhemispheric transfer of memorized positional information has previously been reported in studies assessing the transfer of learning following opposite-arm training in a visuomotor rotation task.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this task is dependent on the interhemispheric transfer of memorized proprioceptive feedback prior to making an accurate matching movement (Fabri et al 2001;Sperry et al 1969), one may logically conclude that subjects more readily transferred this information from the left to the right hemi- sphere. This directional bias with respect to the interhemispheric transfer of memorized positional information has previously been reported in studies assessing the transfer of learning following opposite-arm training in a visuomotor rotation task.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical locations of these regions might depend on the type of information being processed. Indeed, evidence from partial split-brain patients suggests that callosal transfer of somatosensory information occurs between regions of posterior cortex (34)(35)(36), whereas the transfer of other higher level cognitive information might occur between more anterior regions of temporal and frontal cortex (37).…”
Section: Spatiotemporal Interhemispheric Communicationmentioning
confidence: 99%
“…Regardless, these results provided evidence of intermanual transfer of shape in full-term newborns with the hypothesis that the development of the corpus callosum would be sufficient to permit some transfer of shape information between the two hands. Indeed, an fMRI study demonstrated the essential contribution of posterior corpus callosum to the interhemispheric transfer of tactile information (Fabri et al, 2001(Fabri et al, , 2005. Considering that the corpus callosum is less mature in preterm infants than full-term infants (Anderson, Laurent, Woodward, & Inder, 2006) and that very preterm birth (before 33 GW) might be associated with perinatal brain injury including the corpus callosum (Kontis et al, 2009), we wanted to determine if preterm infants are capable of intermanual transfer of shape after the age of 33 GW.…”
mentioning
confidence: 99%